2021
DOI: 10.3892/ol.2021.12769
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of circulating AP001429.1 long non‑coding RNA in obese patients with breast cancer

Abstract: Long non-coding RNAs (lncRNAs), a type of cellular RNA, play a critical regulatory role in several physiological developments and pathological processes, such as tumorigenesis and tumor progression. Obesity is a risk factor for a number of serious health conditions, including breast cancer (BC). However, the underlying mechanisms behind the association between obesity and increased BC incidence and mortality remain unclear. Several studies have reported changes in lncRNA expression due to obesity and BC, indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 79 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…The participants were provided with information concerning the study and requested to sign a consent form. Clinicopathological data were acquired from the Department of Laboratory Medicine and Pathology, KAUH ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…The participants were provided with information concerning the study and requested to sign a consent form. Clinicopathological data were acquired from the Department of Laboratory Medicine and Pathology, KAUH ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…Recent study has indicated that obesity can reduce the expression of lncRNA AP001429.1 in patients with BC, thus promoting cancer progression. 123 Downregulation of lncRNA five prime to Xist (FTX) and overexpression of lncRNA small nucleolar RNA host gene 20 (SNHG20) promoted the development of nonalcoholic fatty liver disease (NAFLD) into HCC by modulating the polarization of Kupffer cells. 124,125 The leptin and estradiol levels in postmenopausal obese women are high, and the two hormones contribute to angiogenesis, survival, cell proliferation, and migration.…”
Section: 11mentioning
confidence: 99%
“…In the context of BC, lncRNA AP001429.1 can target multiple miRNAs, potentially exerting anticancer effects. Recent study has indicated that obesity can reduce the expression of lncRNA AP001429.1 in patients with BC, thus promoting cancer progression 123 . Downregulation of lncRNA five prime to Xist (FTX) and overexpression of lncRNA small nucleolar RNA host gene 20 (SNHG20) promoted the development of nonalcoholic fatty liver disease (NAFLD) into HCC by modulating the polarization of Kupffer cells 124,125 .…”
Section: Ncrnas In Obesity‐associated Diseasesmentioning
confidence: 99%
“…AP001429.1 882 is a lncRNA that may have a protective role against breast cancer. Its expression was measured in obese 883 and non-obese individuals with breast cancer and it was found that AP001429.1 is downregulated in 884 obese patients with breast cancer compared with non-obese individuals with breast cancer [255]. 885 lncRNA-small nucleolar RNA host gene 9 (LncRNA-SNHG9) 886…”
Section: Ap0014291 880mentioning
confidence: 99%